Rural-based tourism and local economic development: evidence from Indonesia - Utomo, Sugeng Hadi; Wulandari, Dwi; Narmaditya, Bagus Shandy; Ishak, Suryati; Prayitno, Putra Hilmi; Sahid, Sheerad; Qodri, Lutfi Asnan (Editura Universitatii din Oradea, 2020)
Dealing with the environmental issue, rural-based tourism is the alternative in enhancing the welfare of the community. This study aims to examine the relationship between rural-based tourism and local economic development, and provides an insight into the development strategies ruralbased tourism. This present paper applied a quantitative approach by utilizing a rapid assessment of local economic development (RALED). Participants of this study were recruited from stakeholders, administrator and the local community in three rural-based tourism in Batu of East Java, Indonesia. The findings indicate that the six dimensions have met the good and excellent category. However, the attention needs to be given to the three least dimensions, including target group, management process and policy focus and synergy. These results suggest that rural-based tourism is strongly linked with the local community due to the community involvement for tourism development.